Physician's awareness of the prevention of corticosteroid induced osteoporosis - Supparat Ungprasert (2018)
Background and Objective: Corticosteroid induced osteoporosis (CIO) is a preventable condition that is often not realized by physicians who prescribe corticosteroids. The present study was carried out to study the awareness of CIO prevention in a teaching hospital. Material and Method: The medical records of patients who received corticosteroids equivalent to prednisolone of ≥ 5 mg/day for a minimum of 3 months between 1 May 2004 and 30 June 2004 were reviewed. Results: Four hundred and forty nine patients of 1,540 who received corticosteroids (29.1%) were included in the present study. Rheumatologists, nephrologists, and dermatologists were the top three specialists to prescribe corticosteroids in 189 (42.1%), 103 (23.0%), and 46 (10.2%) cases, respectively. Only 146 patients (32.5%) received calcium supplement. Rheumatologists and neurologists were the top two specialists to prescribe calcium supplementation in 100 of 189 (52.9%) and 13 of 36 (36.1%) cases, respectively. Bone mineral density measurement was determined in only 26 of the 449 patients (5.8%). Conclusion: Prevention of CIO is still neglected by internal medicine specialists, even in a teaching hospital. An educational campaign for physicians is warranted to improve the practice for the prevention of this treatable complication.